Concentration-Dependent Multi-Potentiality of L-Arginine: Antimicrobial Effect, Hydroxyapatite Stability, and MMPs Inhibition - Mohammed Nadeem Bijle (MDPI AG, 2021)
This study’s objective was to examine L-arginine (L-arg) supplementation’s effect on mono-species biofilm (Streptococcus mutans/Streptococcus sanguinis) growth and underlying enamel substrates. The experimental groups were 1%, 2%, and 4% arg, and 0.9% NaCl was used as the vehicle control. Sterilised enamel blocks were subjected to 7-day treatment with test solutions and S. mutans/S. sanguinis inoculum in BHI. Post-treatment, the treated biofilms stained for live/dead bacterial cells were analysed using confocal microscopy. The enamel specimens were analysed using X-ray diffraction crystallography (XRD), Raman spectroscopy (RS), and transmission electron microscopy (TEM). The molecular interactions between arg and MMP-2/MMP-9 were determined by computational molecular docking and MMP assays. With increasing arg concentrations, bacterial survival significantly decreased (p < 0.05). The XRD peak intensity with 1%/2% arg was significantly higher than with 4% arg and the control (p < 0.05). The bands associated with the mineral phase by RS were significantly accentuated in the 1%/2% arg specimens compared to in other groups (p < 0.05). The TEM analysis revealed that 4% arg exhibited an ill-defined shape of enamel crystals. Docking of arg molecules to MMPs appears feasible, with arg inhibiting MMP-2/MMP-9 (p < 0.05). L-arginine supplementation has an antimicrobial effect on mono-species biofilm. L-arginine treatment at lower (1%/2%) concentrations exhibits enamel hydroxyapatite stability, while the molecule has the potential to inhibit MMP-2/MMP-9.